KONSTRUKSI PEMBERITAAN KASUS PEMBUNUHAN JAMAL KHASHOGGI DI MEDIA BBC NEWS INDONESIA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This research aimed to determine the construction of the news on the murder case of Jamal Khashoggi in the October 2018 edition by BBC News Indonesia media, through Robert N Entman’s framing analysis model approach. This research was a descriptive qualitative analysis of media text, used the Robert N Entman framing analysis model. The data collecting techniques in this research used documentation, observation, and literature review. The data analysis technique was carried out in four stages of Robert N Entman's framing analysis, namely, define the problem, diagnose causes, moral evaluation, and recommendation. The results of this study showed that BBC News Indonesia highlighted the case of Jamal Khashoggi‘s premeditated murder by accusing the Saudi Arabian government as the causing problem actor, the inconsistent statements of the Saudi Arabian government appeared international criticism and urged to explain openly and factually related to the murder case of Jamal Khashoggi The implication of this research it can contribute for enriching media research knowledge, especially which regard to framing research. In addition, this research can be useful for the general public to be more active and selective in choosing the news to read, and specifically for the news media so that they can produce the worth of reading news and not only as reading material but also as a lesson for the readers.